PEMODELAN DAN SIMULASI KEBIJAKAN DENGAN PENDEKATAN SYSTEM DYNAMICS 1 Kasus Permintaan Air PDAM di Salatiga - Ariyani, Yayuk; Saleh, Samsubar; Fevriera, Sotya (Universitas Muhammdaiyah Surakarta, 2010)
About 58,83 percent of Salatiga population consumes water from PDAM (Peru- sahaan Daerah Air Minum) to fulfill their daily need. The demand for water, which is increasing in line with infrastructure development and economics growth in Salatiga while the availability of water is decreasing, lead to a lack of water in some regions in Salatiga. Therefore, a new policy is needed to solve this problem. Before that, a simulation of the policy is needed because it is not possible to do a direct research on the policy. Thus, this recent study attempts to model the phenomenon of demand for water in Salatiga with dynamics system approach since it can be used for a policy simulation. Based on the simulation result, it is suggested to solve the water scarcity problem by trying to reduce the rate of leaking in water distribution from 26 percent to 5 percent.